Mistakes in Personal Identification Attempts - Fenyvesi, Csaba (Magyar Rendészet, 2024)
The following study is meant to present the most frequent mistakes (dangers) of identity parades (line-up, recognition) and their possible consequences, such as for instance the worst outcome: justizmord, (miscarriage of justice). The author analyses sources of criminal tactical and criminal technical major errors through real international and Hungarian homicide cases and suggests legislative changes “de lege ferenda” as well as preventive methods and tactics for law enforcers and criminalists as well.